A preliminary study of possible fibrotic role of meprin metalloproteases in scleroderma patients - Ayşe Koçak; Aydan Köken Avşar; Duygu Harmancı; Gül Akdoğan; A. Merih Birlik (Archives of Rheumatology, 2021)
Objectives: This study aims to investigate the possible fibrotic role of meprin metalloproteases and possible fibrotic effects of activator protein-1 (AP-1) in scleroderma patients. Patients and methods: Between April 2018 and April 2019, a total of 85 scleroderma patients (9 males, 76 females; mean age: 54.9 years; range, 22 to 80 years) who met the 2013 American College of Rheumatology/European League Against Rheumatism criteria and 80 healthy control individuals (10 males, 70 females; mean age 42.9 years; range, 19 to 65 years) were included. Patients’ data and blood samples were collected. Messenger ribonucleic acid expressions of interleukin (IL)-6, AP-1 subunits, and tumor necrosis factor-alpha (TNF-α) were analyzed by quantitative real-time polymerase chain reaction. Serum meprin alpha and beta protein levels were analyzed using the enzyme-linked immunosorbent assay. Results: Meprin alpha and meprin beta protein levels increased in scleroderma patients. The AP-1 subunits (c-Fos, c-Jun), IL-6, and TNF-α increased in scleroderma patients, compared to controls. Conclusion: Our results provide evidence showing that increased meprins levels may be related to AP-1 levels and increased meprins levels may responsible for increased inflammatory TNF-α and IL-6 levels. All these data suggest meprins as promising therapeutic targets to restore the balance between inflammation and extracellular matrix deposition in scleroderma.